ANALYSIS OF STUDENTS' LOGICAL THINKING SKILLS IN COMPUTER PROGRAMMING LEARNING - Asnurul Isroqmi; Allen Marga Retta; Tika Dwi Nopriyanti (Sriwijaya University Learning and Education International Conference, 2018)
This study aims to describe students' logical thinking skills in computer programming learning on algorithmic and programming subjects. The purpose of learning computer programming is to make a program that can do a calculation or "work" in according to the programmer desire. Programming requires some skill, namely; logic, algorithms and programming. Logic in programming is one of the supporters of success in making computer programs. For this reason, it is necessary to have indicators or measuring instruments to see whether students understand the making of a program, namely by: 1) Harmony of thinking, 2) Ability to argue, and 3) Drawing conclusions. This research is quantitative descriptive. The subjects used in this study were students of the PGRI Palembang 2017/2018 academic year. The data collection technique used is a test. Data is analyzed through data reduction, data presentation, and conclusion drawing. The results of the study show that: 1) In the indicator of thinking harmony, students can determine the steps taken regularly in solving problems given from the beginning of planning to obtain a conclusion, 2) On indicators of argumentation ability, students can give logical arguments according to facts or existing information related to the problem planning step and solving the problem taken, 3) On the indicators of drawing conclusions, students can draw a conclusion from an existing problem based on the steps that have been taken